Association of Parental Awareness of Using Schoolbags With Musculoskeletal Symptoms and Carrying Habits of Schoolchildren. (December 2014) - Dianat, Iman; Karimi, Mohammad Ali
The association between parental awareness of using schoolbags and the occurrence of musculoskeletal symptoms and carrying habits of children was investigated in a cross-sectional study in Tabriz, Iran. Data on 454 students aged 11−14 years and their parents ( n = 358) were analyzed. The awareness of the recommended weight limit, appropriate method of carrying schoolbags, and schoolbag strap adjustments was generally low among the respondents. A higher parental awareness of the schoolbag weight was associated with a lower prevalence of upper back and shoulder complaints among children and carrying loads less than 10% of their body weight. The findings suggest that parental awareness should have a more prominent role in changing the schoolbag carrying habits of children and particularly in reducing the weight of loads carried by them. This highlights the need to incorporate guidelines and recommendations into practice to ensure that the health and safety of schoolchildren are not compromised when using schoolbags.